Chemical analysis of wild edible mushrooms from the South-Western Amazon - Santos, Geyse Souza; Souza, Bruno Jhosef Freires de; Brandão, Ludmilla da Silva; Menezes, Rui Santana de; Carvalho, Clarice Maia (Acta Scientiarum. Biological Sciences, 2024)
Edible mushrooms are widely studied because they have nutritional and medicinal properties, being considered a good source of protein, with an amount comparable to animal protein and low in fat. Due to the presence of specific bioactive compounds in mushrooms, they have a high therapeutic value in strengthening the immune system and preventing diseases and can be considered highly functional foods. Thus, the objective of this work was to evaluate the nutritional composition of wild mushrooms from the South-western Amazon. Two fungal samples that showed low cytotoxicity against HepG2 in a previously done assay were used. To obtain mycelium, the isolated mushrooms were grown in Petri dishes with 20 mL of Potato-Dextrose-Agar and incubated at 28 ºC for 14 days. After this period, the mycelium was transferred to Erlenmeyer flasks containing 200 mL of Potato-Dextrose medium in a 10% proportion, for growth for another 14 days at 28 °C, without agitation. Then, the mycelium was separated from the liquid medium and dried for 24 hours in an oven at 37 °C, and then weighed and ground to do chemical analysis. Moisture, ash, lipids, proteins and carbohydrates from mushrooms 5.332 Oudemansiella cubensis and 5.358 Hohenbuehelia sp. were analyzed according to the methodologies of Instituto Adolfo Lutz [IAL] in triplicates. As a result, mushroom 5.332 O. cubensis had 11.12% moisture, 33.75% lipids, 2.90% ash, 47.27% protein and 9.97% carbohydrates, while mushroom 5.358 Hohenbuehelia sp. had 5.14% moisture, 26.38% lipids, 3.11% ash, 59.11% proteins and 6.26% carbohydrates. The Amazonian mushrooms analyzed in this work are rich in proteins and lipids, however they have a low carbohydrate content and can be considered potential sources of functional ingredients. This study contributes to the first report on the nutritional analysis of Oudemansiella cubensis and Hohenbuehelia sp.